DETERMINAN CARBON EMISSION DISCLOSURE DI INDONESIA - Yusuf, Muhammad (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2020)
Global and uncontrolled climate change has caused a variety of problems and has become one of the biggest environmental issues in recent years. Indonesia is the fifth largest carbon emitting country in the world and as a country that has signed the Kyoto Protocol must participate in efforts to reduce carbon emissions. According to the Ministry of Environment and Forestry, industry is one of the biggest contributors to carbon emissions. This is one of the reasons why companies (industries) must contribute to reducing carbon emissions. Efforts made by companies are to do carbon emission disclosure. Carbon emission disclosure in Indonesia is still a voluntary disclosure so that not all companies make disclosures in their financial statements. This study aims to obtain empirical evidence about the factors that drive companies to conduct carbon emission disclosure. The determinant variables of carbon emission disclosure in this study are profitability, leverage, environmental performance, company size, and corporate governance, by taking samples of companies listed on the Corporate Governance Perception Index (CGPI) for the period 2007-2017. Determination of the research sample using purposive sampling method and data analysis techniques using the multiple linear regression method. The results showed that profitability, environmental performance, company size, and corporate governance had a positive effect on carbon emission disclosure while leverage had no effect on carbon emission disclosure. This research contribution provides empirical evidence about profitability, environmental performance, company size, and corporate governance are factors that drives companies to do carbon emission disclosure in Indonesia.